Non-carious cervical lesions of tooth with associated factors - Kumar Singh, Amit; Lama Tamang, Sagar; Kumar Roy, Saurabh (Journal of Chitwan Medical College, 2024)
Background:Non-Carious Cervical Lesions (NCCLs) are characterized by the loss of teeth structures in the cervical area that are not related to caries. The purpose of this study was to investigate factors related to NCCLs. The primary aim of this study was to assess the presence of NCCLs among the general population of the Residents of Biratnagar and the potential association with patient-related risk factors.Methods:A prevalence study of NCCLs included 96 respondents from residents of Biratnagar seeking Dental care. NCCLs were diagnosed according to the Smith and Knight tooth wear index, measured using a Williams periodontal probe. Data regarding risk factors were obtained through a structured questionnaire. Patient’s demographic data were analyzed using descriptive statistics. Categorical variables were tested using the chi-square test.Results:Non-Carious Cervical Lesions (NCCLs) were diagnosed in 49.4% of participants. Statistically significant differences in the prevalence of NCCLs were found according to Age(p